Exodus! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Migration is sometimes a calculated grab at a better life, sometimes a horrified flight from killing fields, or an escape from fields that feed too few. It is both a cause and an effect of change in ACP agriculture and rural life, a symptom full of...